Tactile Sensing Fingers Device Using Quantum Tunneling Composite (QTC) Pills - Aqilah Ahmad, Ahsana; Izzah Lina Azman, Nur; Azmi Ayub, Muhammad (International Journal of Engineering and Technology, 2018)
This study investigated the potential of a material namely Quantum Tunneling Composite (QTC) pills as a tactile sensor. The properties and potential of QTC pill motivate this study to develop a new tactile finger device to increased muscle strength and functional ability of the hands. This is due to the health problems involving hand such as a stroke, Parkinson and carpal tunnel syndrome have difficulties to remain stable when grasping objects. QTC is a smart polymer matrix composite and a unique material. It acts as an insulator but in the highest compression exerted, it acts as a conductor. This is due to no electron can pass through this material when there is no compression. The experiments were conducted to investigate the sensitivity of the pills by plotting Force vs. Resistance graph. It is found out that these pills are capable to detect variation of force changing between 0gF to 500gF within 5seconds after loads are applied to the pills. In addition, the sensor glove device had also been designed using QTC Pills as a tactile sensor. Then, the prototype is used to evaluate three several types of gripping touches which are no gripping touch, light gripping touch, and heavy gripping touch of sphere shape objects (61.4g). The sensor should be able to detect the slightest changes in force exerted to the ball using this simple grapping action. The re-sults are visualized by using myRIO hardware and labVIEW software. Force values of the gripping action are recorded for each finger; thumb, index, middle, ring and small finger. This work hopefully be able to assist in a rehabilitation process and use as a measurement tool to quantity the patientâ€™s hands gripping ability when compared to a healthy person.Â Â